TEACHING A SENTENCE IN EFL CLASSES AND METHODOLOGY - Olimova (Isroilova ) Sadoqat; Igamberdieva Shahnoza (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
In this article, we are going to identify ways to teach sentence-making techniques in English grammar. As usual, sentence theory is given and studied in grammar in the syntactic part, but modern teaching methods require language in action, i.e. communication is better than learning a language according to grammatical rules. Currently, one of the main problems is teaching grammar of a foreign language. Proper use of grammar is essential for proper communication of messages.